2023
DOI: 10.3390/app13031566
|View full text |Cite
|
Sign up to set email alerts
|

Earthquake Magnitude and Frequency Forecasting in Northeastern Algeria using Time Series Analysis

Abstract: This study uses two different time series forecasting approaches (parametric and non-parametric) to assess a frequency and magnitude forecasting of earthquakes above Mw 4.0 in Northeastern Algeria. The Autoregressive Integrated Moving Average (ARIMA) model encompasses the parametric approach, while the non-parametric method employs the Singular Spectrum Analysis (SSA) approach. The ARIMA and SSA models were then used to train and forecast the annual number of earthquakes and annual maximum magnitude events occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 98 publications
0
1
0
Order By: Relevance
“…Briefly, the estimation results â = −8.13277 and b = 21.37195. In addition, we also compare the model in Equation ( 19) with the autoregressive integrated moving average (ARIMA) (1, 1, 1) model, as follows [64]:…”
Section: Extreme Earthquake Frequency Processmentioning
confidence: 99%
“…Briefly, the estimation results â = −8.13277 and b = 21.37195. In addition, we also compare the model in Equation ( 19) with the autoregressive integrated moving average (ARIMA) (1, 1, 1) model, as follows [64]:…”
Section: Extreme Earthquake Frequency Processmentioning
confidence: 99%
“…For AFAD, it is reported that ML and M w scales are almost equivalent for a wide range of magnitude values (see [78] and references therein); thus, this catalog could be considered homogeneous with respect to magnitude (cf. a unified EQ catalog is necessary for this kind of analysis, see, e.g., [79]). There, beyond the cumulative FMD depicted by open squares, the noncumulative FMD [80] is also shown with open triangles.…”
Section: The Seismic Data Usedmentioning
confidence: 99%
“…Its ability to analyze seasonality, periodicity, and trends in data make it highly versatile with accurate predictive effect. It has been utilized for morbidity prediction in medical research [29,30], commodity price and stock price forecasting in finance [31][32][33][34], as well as for applications in geology [35,36], transportation [37,38], electricity [39,40], sound recognition [41], atmospheric environment research [42], and other disciplines. In recent years, the rapid development of big data and artificial intelligence has led to long short-term memory (LSTM), a modified version of a recurrent neural network (RNN), becoming a prominent research topic.…”
Section: Regulated or Suggested Concentration Of Co 2 (Ppm)mentioning
confidence: 99%